2018
DOI: 10.3892/mmr.2018.9777
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol inhibits multiple pathways involved in the secretion of inflammatory mediators from LPS‑induced rat intestinal microvascular endothelial cells

Abstract: Inflammatory bowel disease (IBD) is a chronic, idiopathic inflammatory disease of the small and/or large intestine. Endothelial expression of inflammatory mediators, including cytokines and adhesion molecules, serves a critical role in the initiation and progression of IBD. The dietary flavonoid, kaempferol, has been reported to inhibit expression of inflammatory mediators; however, the underlying mechanisms require further investigation. In the present study, a novel molecular mechanism of kaempferol against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Kaempferol can inhibit the inflammatory response induced due to endotoxins in acute lung injury in mice as well as in cellular models [172]. The inhibition of the expression of inflammatory mediators was demonstrated in a cellular model of intestinal inflammation in rats [173]; further, anti-inflammatory effects were observed on the inflammation induced by Helicobacter pylori [174]. In addition, antidepressant effects [175] and improvement of wound healing in diabetic and non-diabetic rats [176] have also been attributed to kaempferol.…”
Section: Bioactivity Of Crocus Sativus L Compoundsmentioning
confidence: 99%
“…Kaempferol can inhibit the inflammatory response induced due to endotoxins in acute lung injury in mice as well as in cellular models [172]. The inhibition of the expression of inflammatory mediators was demonstrated in a cellular model of intestinal inflammation in rats [173]; further, anti-inflammatory effects were observed on the inflammation induced by Helicobacter pylori [174]. In addition, antidepressant effects [175] and improvement of wound healing in diabetic and non-diabetic rats [176] have also been attributed to kaempferol.…”
Section: Bioactivity Of Crocus Sativus L Compoundsmentioning
confidence: 99%
“…Various pharmacological studies showed that isorhamnetin protects against cardiac hypertrophy and can exhibit positive effect on hypoxia/reoxygenation-induced injury by attenuating apoptosis and oxidative stress [25,26]. Kaempferol can inhibit inflammatory responses and exert protective effect in LPS-induced microvascular endothelial cells [27]. Besides, the protective effect of kaempferol on heart in isoproterenol-induced heart failure has also been proven [28,29].…”
Section: Discussionmentioning
confidence: 98%
“…The level of TFF3 mRNA as a functional marker of goblet cells was also up-regulated [ 35 ]. Similarly, the intestinal inflammatory cell model induced by LPS also showed that kaempferol significantly reduced the excessive secretion of TNF-α, IL-1β, IL-6 and ICAM-1, indicating the negative regulation of TLR4, NF-kappaB and STAT signal transduction pathways [ 36 ].…”
Section: Discussionmentioning
confidence: 99%